A bio‐safe cyclophosphazene derivative flame retardant for polylactic acid composites: Flammability and cytotoxicity. (20th October 2020) - Xue, Qingxia; Wu, Quan; Yao, Yuan; Li, Xinjian; Sun, Jun; Gu, Xiaoyu; Song, Weiguo; Yan, Fang; Zhang, Sheng
Abstract : An efficient bio‐safe cyclophosphazene flame retardant, 1, 5, 9, 13, 16, 20‐Hexaoxa‐7, 14, 21‐triaza‐6 λ 4, 8 λ 4, 5 λ 4 ‐triphosphatrispiro[5.1.5.1.5.1]heneicosa‐6, 8(14), 15(21)‐triene (HCPO), was synthesized, and then was incorporated into polylactic acid (PLA) to improve the fire safety. The chemical structure of HCPO was confirmed by Fourier‐transformed infrared spectroscopy, mass spectrometry, and nuclear magnetic resonance spectroscopy. The thermal stability of the compound was characterized by thermogravimetric (TG) analyzer. The cytotoxic effects of HCPO to cells were evaluated. Fire behavior and thermal stability of PLA composites were investigated by vertical burning, limiting oxygen index (LOI), TG analysis, and cone calorimeter. The morphology of residual charring was observed by scanning electron microscope. The results showed HCPO was bio‐safe, and highly effective to enhance the flame retardancy of PLA composites. The LOI value was increased from 18.4 to 27.5 and UL‐94 grade achieved V‐0 for the PLA composite containing only 2% HCPO and 2% pentaerythrotol. It was demonstrated that intermolecular cross‐linking reaction between pentaerythrotol and HCPO in high temperature range could accelerate the formation of compact char layers.